Exploring co-infection dynamics and immune response interactions between COVID-19 and Monkeypox: implications for disease severity, viral transmission, and vaccine efficacy - Oluwatoyin Ayo-Farai; Nenrot Gopep; Aminat Alarape-Raji; Huda Adnan; Maryam Ahmed; Rida Arif; Eisha Kashif; Malik Olatunde Oduoye; Muhammad Usman Haider (Virology Journal)
Abstract Background Coronavirus disease (COVID-19) and Monkeypox (Mpox) are viral infections that have similar modes of presentation, diagnosis and treatment strategies. Understanding their co-infection dynamics and immune response is important for public health policies. Aim This article aims to determine the relationship between dynamicity and immune response interactions between Mpox and COVID-19, focusing more on the implications for disease severity, viral transmission, and vaccine efficacy. Methodology An extensive literature review was conducted through electronic databases including PubMed, Google Scholar and Web of Science from the last decade (2014–2024) using keywords: COVID-19, Co-infections, Immune response, Monkeypox, and Vaccination. Results Several co-infections between COVID-19 and Mpox have been reported, especially a case from Florida, in the United States of America (USA), in Barcelona, Spain (a 56-year-old man who suffered both Mpox and COVID-19 and syphilis simultaneously, and from Italy (a 36-year-old male). Both COVID-19 and Mpox have been shown to have some effects on the immunity of a person, especially the innate system, which can occasionally produce inadvertent effects. A common factor that links the two diseases is the endoglycosidase named Heparanase (HPSE). Both COVID-19 and Mpox clinical features have bizarre severity and complications. The rising co-infection of COVID-19 and increased Mpox infection rate has led to the development of only approved vaccines JYNNEOS and COH04S1. Conclusion Global efforts such as adequate awareness campaigns through webinars, social media platforms, and research, including experimental studies, cohort studies, case series, etc., should be put in place to give more insights into both diseases. Such efforts should be backed up with good political will, adequate funding, the establishment of research facilities and interprofessional measures among the concerned countries and policymakers in the world.